Variability assessment in M7-lines of fenugreek (Trigonella foenum-graecum L.) - Dashora, Surendra Kumar Kaushik, S L (Journal of Spices and Aromatic Crops, 2001)
The variability in 29 M-lines derived from gamma radiation at 10, 20, 30, 40 and 50 Kr dose along with three checks namely, RMt-1, RMt-143 and a local cultivar of fenugreek (Trigonella foenum-graecum) was estimated. Significant variability was recorded for days to flowering, plant height, pods per plant, seeds per pod, test weight, seed yield per plot, protein content and the incidence of powdery mildew disease. High genotypic and phenotypic coefficients of variation were observed for protein content, pods per plant, seed yield per plot and branches per plant. High broad sense heritability (>74%) coupled with high genetic advance (>31 %) was recorded for protein content and pods per plant. Among the 29 M,-lines, No. 20 (551-1) exhibited superiority over all the three checks and other lines, indicating the necessity for further evaluation of this line.